Recurrent pulmonary thromboembolism with cardiac tamponade as initial manifestations of lupus and antiphospholipid syndrome: a case report - Villanueva-Valle, Julieta Sofia (2024)
Systemic lupus erythematosus (SLE) is an inflammatory autoimmune disease with an important course due to systemic compromise. SLE is frequently associated with antiphospholipid syndrome, and pulmonary thromboembolism (PE) is particularly common. It is extremely rare for PE to be the initial clinical presentation and even more uncommon for it to coincide with cardiac tamponade, representing a challenge in diagnosis and management. We present a case of a 42-year-old woman with recurrent PE with severe pleural and pericardial effusion, hemodynamic instability, and cardiac tamponade. Laboratory workup revealed hypocomplementemia, leukopenia, negative SLE antibodies, and a positive lupus anticoagulant. This case emphasizes the importance of determining the etiology of PE, assessing risk classification, and implementing proper management, which are crucial for the patient's survival and outcome.